Pengaruh Employer Branding terhadap Retensi Pegawai dengan Job Satisfaction, Organizational Identification serta Career Development sebagai mediator: Studi Pada Pekerja Perusahaan Teknologi - Pricilla, Karina; Martdianty, Fanny (Jurnal Manajemen dan Usahawan Indonesia, 2024)
This study aims to investigate the effect of employer branding on employee retention with the mediating role of job satisfaction, organizational identification, and career development. This research uses a quantitative method using a questionnaire survey involving 400 workers in Jabodetabek technology companies. Data processing was carried out using Structural Equation Modeling (SEM) with Lisrel 8.8 software and it was found that employer branding has a significant influence on job satisfaction, organizational identification, and career development. However, of the three mediations used, only one had a significant effect, namely job satisfaction. Thus, this study shows that although employer branding has a positive effect on other variables, only job satisfaction has a mediating role on employee intention to stay in Jabodetabek technology companies.